A Cognitive Perspective on Policy Implementation: Reform Beliefs, Sensemaking, and Social Networks. (28th June 2017) - Siciliano, Michael D.; Moolenaar, Nienke M.; Daly, Alan J.; Liou, Yi‐Hwa
Abstract: Utilizing a cognitive perspective, this article examines the social processes through which teachers come to understand the Common Core State Standards. The authors begin by identifying three beliefs that have important implications for policy implementation: self‐efficacy, resource adequacy, and value for clients. They measure those beliefs and the Common Core discussion networks that emerge among teachers at three points in time. Through the use of SIENA models, the authors explore how networks and beliefs coevolve within schools. Unlike prior research on social networks, which consistently finds strong homophilous tendencies, this research finds no evidence that teachers seek out coworkers who hold similar beliefs. Rather, teachers relied on preexisting formal and informal relationships to guide interactions. Those interactions were characterized by social influence, whereby a teacher's own beliefs adapted toward the beliefs held by the members of their social network. The findings offer a novel perspective on the complex dynamic that occurs within organizations as new policies are unveiled and employees interact with one another to understand the changes those policies entail . Abstract : Related Content:Vodicka (PAR November/December 2017)